One-stop border posts and informal livelihoods in Busia, Kenya. Issue 4 (19th May 2018) - Tyson, Judith E.
ABSTRACT: 'One-stop border posts' (OSBP) are being developed on East African trade corridors to support growth in cross-border trade in the region. This article presents a household survey examining the impact of the OSBP at Busia on the Kenya–Uganda border on the livelihoods of informal traders and workers. It finds positive effects through enhanced access to cross-border trade. However, it also finds negative effects, including reduced work opportunities for unskilled manual workers. Further research is needed into the long-term effects on the price and foreign exchange differentials which currently incentivise the informal trade, before the effects can be fully assessed.